Palestinian Liberation Theology, Christian Zionism, and the Agency of Arabic-Speaking Evangelicals in Israel - Kirchner, Anna Maria (Implicit religion, 2023)
This paper explores how Arabic- speaking Evangelicals in Israel navigate between two competing theological discourses that claim to speak for them: Palestinian Liberation Theology and Christian Zionism. Palestinian Liberation Theology, advocating justice and self- determination, dominates public perceptions of all Christians in Israel- Palestine, performing and demanding a unified Palestinian identity. Yet Arabic- speaking Evangelicals face a twofold dilemma: as Israeli citizens, their national identity is contested; as Evangelicals, they are globally associated with Christian Zionism. Rather than aligning with either discourse, most emphasize a "heavenly identity" centered on Christ and salvation, as my fieldwork in Nazareth (2016-2018) demonstrates. Drawing on Saba Mahmood’s concept of agency, this paper argues that this positioning is not apolitical withdrawal but strategic resistance within severely constrained structures. By refusing appropriation from both Palestinian nationalist theology and Christian Zionism, Arabic- speaking Evangelicals articulate a subversive critique, insisting on fundamental evangelical concerns over nationalist theological claims.